A voz de Capitu na crítica-ficção: relações entre Dom Casmurro e Capitu – memórias póstumas - Cardoso, Rosângela Aparecida (2013)
This thesis investigates the reception of Capitu, the character of Machado de Assis, by Capitu – memórias póstumas (1998), the criticism-fiction of Domício Proença Filho, in an attempt to explain, in the field of intertextuality, the notion of author, emphasizing how, a century later, Capitu‟s ressignifications are connected with the aesthetic and ideological context of the end of the 20th century. The attempt of examining, in Dom Casmurro (1899), the affirmation of the character-writer: “everything is found out of a faulty book, friendly reader. So I fill out somebody else's gaps; so you can fill out also mine”, and the attempt to investigate, in Capitu – memórias póstumas, the substitution of the moody-author by the character-writer Capitu, takes us to the problematic of the metafiction. Our scope lies on how the questions of the authorship, of the reader, of the reading and of the parody are interconnected, owing to the fact that Proença‟s novel provokes, in itself, its own aesthetic problematization related to the interference of the point of view in the narrated facts, inviting us to rethink, with him, Machado‟s novel with the voice of Capitu, and as a consequence of that, to rethink Capitu as a character. Such procedure takes us to the critical and theoretical field of investigation, seen as a more recurrent path towards fiction since the end of the 20th century